Determinan Determinant Factors of Self-Efficacy Among Nurses on Implementation of Discharge Planning Inpatient Room at Wangaya Regional Hospital - Ni Luh Putu Mira Santana Sari; I Gede Putu Darma Suyasa; I Kadek Nuryanto; Putu Noviana Sagitarini (Faculty of Nursing, Universitas Jember, 2023)
Self-efficacy of implementing nurses is a nurse's confidence and ability to carry out discharge planning that aims to improve the quality of health that will affect the sustainability of sustainable care in patients. The goal of the study was to identify determinants of self-efficacy of implementing nurses and analyze the most dominant factors for discharge planning implementation. The design used in this study was cross-sectional with a sample number of 187 implementing nurses selected through simple random sampling using questionnaires as instruments. Data is univariate, bivariate with chi square test, and multivariate with binary logistic regression test. The results of bivariate analysis of burnout variables (p value 0.002) and self esteem (p value <0.001) have a significant influence on discharge planning implementation while multivariate analysis results show that burnout and self esteem variables have the most dominant influence in discharge planning implementation. It is expected that the implementing nurse can increase the value of self-efficacy in themselves through improving good self-function so that it has an impact on the quality of service in the implementation of discharge planning.